GEOLOGY OF E-FIELD LIMESTONES IN CENTRAL LUCONIA WITH EMPHASIS ON EFFECTS OF DISSOLUTION ON PORE NETWORK STRUCTURE - TAN , SU QUIN (Universiti Teknologi PETRONAS, 2014)
Central Luconia Province is characterized by its abundance of Miocene carbonate buildups and gas production. Many studies have been undergone to understand and evaluate the diagenetic history and reservoir character through seismic, sedimentology and stratigraphy. However, many of the works are unpublished and little is known on the carbonate geology and sedimentology of E-field limestones and their dissolution chemistry. The complexity in pore systems of carbonates is mostly due to the biological origin of carbonate sediments and their chemical reactivity. Therefore, understanding of fabric, texture, porosity and petrophysical properties is crucial in hydrocarbon exploration and production. The projects aims to understand the facies and fabric of the rock and how does it relate to its depositional environment and diagenetic history subsequntly, the behaviour of pore network to acid dissolution. Fieldmapping is also carried out on an outcrop in Sungai Siput,Perak as an analog model for our offshore sample. 2 well cores taken from offshore E-field of Central Luconia is used for this study. Modelling of the pore structure of the rock pre- and pra- dissolution is carried out using CT-scan with the help from SEM. 3 major facies has been identified with the help of thin section, core observation, XRD, SEM and CT Scan. Poro-perm analysis showed that the porosity in these rocks range from fair-good and permeability poor-fair. Depositional environment interpretation showed that the rocks are deposited in the shallow marine subtidal environment, lagoonal to shallow water platform margin. In conclusion, the study shows that the fabric, texture and pore type of the rock is very much related to its depositional history. It is noted that these rocks will thus behave differently to acid dissolution because of their heterogeneity.